Penggunaan Tanda Tangan Digital dalam Pembuatan Akta Notaris Menurut Perspektif Hukum Progresif - Anita Amalia; Anang Shophan Tornado (AHKAM, 2026)
Although digital transformation in notarial practice has received attention in various previous studies, research that specifically discusses the weaknesses of conventional signatures and the feasibility of digital signatures as their replacement from the perspective of progressive law remains limited. This study aims to analyze the weaknesses of conventional signatures in the preparation of notarial deeds and to assess the feasibility of digital signatures as an alternative replacement based on the perspective of progressive law. This study used a normative juridical method with statutory and conceptual approaches. Data were collected through library research on primary, secondary, and tertiary legal materials, and then analyzed using descriptive qualitative techniques. The results showed that conventional signatures have fundamental weaknesses. Philosophically, conventional signatures are contrary to substantive justice because they may discriminate against people in remote areas and persons with disabilities. Juridically, conventional signatures are vulnerable to forgery and denial, lack a non-repudiation mechanism, and may lead to the degradation of the legal force of authentic deeds. Sociologically, conventional signatures create structural exclusion and inefficiency in notarial services. Practices in the United States, Germany, France, Belgium, Estonia, and Singapore show that digital signatures have been implemented in notarial systems using varied approaches. These findings contribute to the development of notarial law theory and expand understanding of legal reform in the digital era. The conclusion of this study affirms that regulatory harmonization between the Notary Office Law and the Electronic Information and Transactions Law is an important prerequisite for the implementation of digital signatures in notarial deeds. The implications of this study include theoretical contributions to the development of notarial law literature and practical implications for the government in explicitly revising the Notary Office Law and strengthening the digital infrastructure of notarial practice.